The mitochondrial genome of Prays oleae (Insecta: Lepidoptera: Praydidae). - Asch, Barbara (2015)
Prays oleae is one of the most important olive tree pests and a species of interest in evolutionary studies, as it belongs to one of the oldest extant superfamilies of Ditrysian Lepidoptera. We determined its mitogenome sequence, and found it has common features for Lepidoptera, e.g. an 480% A + T content, an apparent CGA start codon for COX1 and an ATAGA(T)n motif in the control region, which also contains several copies of a 163-164 bp repeat. Importantly, the mitogenome displays the Met-Ile-Gln tRNA gene order typical of Ditrysia, consistent with the hypothesis that this is a synapomorphy of that clade.